The Influence of Job Description and Organizational Culture on Employee Satisfaction at PT Bank Rakyat Indonesia (Persero) Tbk Unit Singosari, Malang - Wahyudi, Eko Juni (Universitas Pamulang, 2023)
Job satisfaction issues are also inseparable from the daily lives of PT. Bank Rakyat Indonesia (Persero), Tbk. Singosari Unit, Malang. It can be seen that job satisfaction is still not fulfilled. The objectives of this study were (1) to determine and analyze the influence of job descriptions and organizational culture on employee job satisfaction partially, (2) to identify and analyze the effect of job descriptions and organizational culture on employee job satisfaction simultaneously, and (3) to know and analyze the dominant influence on employee job satisfaction. In this study the population is all employees of PT. Bank Rakyat Indonesia (Persero), Tbk. The Singosari Malang Unit has a total of 31 people and all of them will be used as research samples or called Quota Sampling. Quota Sampling states that the sample component is the same as the composition of the population with regard to the characteristics of interest. From the research results it can be seen that (1) Job description variable and organizational culture partially significant effect on employee job satisfaction. (2) Job description variable and organizational culture has a significant effect simultaneously on employee job satisfaction. (3) Job description variable is the most dominant variable influencing employee job satisfaction.